Stereotactic ablative radiotherapy for hepatocellular carcinoma: A systematic review and meta‐analysis of local control, survival and toxicity outcomes. Issue 7 (15th August 2021) - Shanker, Mihir D.; Moodaley, Pereshin; Soon, Wei; Liu, Howard Y.; Lee, Yoo Young; Pryor, David I.
Summary: There is a growing body of literature supporting the use of stereotactic ablative body radiotherapy (SABR) in the management of primary hepatocellular carcinoma (HCC). This systematic review and meta‐analysis of the current published evidence for SABR for HCC assessed the impact of treatment dose, fractionation and tumour size on the outcomes of local control (LC), overall survival (OS) and toxicity. A systematic search was independently performed by two authors for articles published in peer‐reviewed journals between January 2005 and December 2019. A DerSimonian and Laird random effects model was used to assess pooled results. A multivariate meta‐regression analysis incorporated the effect of explanatory variables (radiation dose in EQD2[10], fractionation and tumour size) on outcomes of OS, LC and toxicity. Forty‐nine cohorts involving 2846 HCC patients with 3088 lesions treated with SABR were included. Pooled 1‐, 2‐ and 3‐year LC rates were 91.1% (95% confidence interval [CI] 88.3–93.2), 86.7% (95% CI 82.7–89.8) and 84.2% (95% CI 77.9–88.9) respectively. Pooled 1‐, 2‐ and 3‐year OS rates were 78.4% (95% CI 73.4–82.6), 61.3% (55.2–66.9) and 48.3% (95% CI 39.0–57). Population‐weighted median grade 3 toxicity rates were 6.5% (IQR 3.2–16) and mean grade 4/5 rates were 1.4% (IQR 0–2.1). Within EQD2[10] ranges of 40 to 83.33 Gy corresponding to common dose‐fractionation regimens of 30–50 Gy in 5 fractions, there was a multivariate association between superior LC and OS with increasing EQD2[10], with a proportionately smaller increase in grade 3 toxicity and no association with grade 4/5 toxicity. Stereotactic ablative body radiotherapy is a viable treatment option for HCC with high LC rates and low rates of reported grade 3/4 toxicity. Increasing EQD2[10] was associated with improvements in LC and OS with a comparatively smaller increase in toxicity. Prospective randomised trials are warranted to define optimal patient selection and dose‐fractionation regimens.